2020
DOI: 10.29050/harranziraat.669266
|View full text |Cite
|
Sign up to set email alerts
|

Şanlıurfa ilinde besiye alınmış farklı sığır ırklarının besi performanslarının ve karkas özelliklerinin karşılaştırılması

Abstract: melezi ırkı sığırlara ait besi performansları ile karkas özellikleri (yağsız sıcak karkas ağırlığı ve karkas randımanları) araştırılmıştır. Araştırmanın veri setini Şanlıurfa ilinde özel bir işletmeden elde edilen tartım ve sıcak karkas ağırlıkları oluşturmuştur. Kesim ağırlıkları, yağsız sıcak karkas ağırlıkları, karkas randımanı ve günlük canlı ağırlık artışı sırasıyla

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Koc (2016) reported that the average of the carcass weight was 341.89±4.34 kg for Simmental breed. Pinarbasi and Yazgan (2020) reported that the carcass weight of Brown Swiss was lower, statistically (306.21±2.783 kg). In the same study, the carcass weight of Charolais was given as 323.22±7.333 kg, which is approximately 40 kg lower than the average obtained in our study.…”
Section: Resultsmentioning
confidence: 95%
“…Koc (2016) reported that the average of the carcass weight was 341.89±4.34 kg for Simmental breed. Pinarbasi and Yazgan (2020) reported that the carcass weight of Brown Swiss was lower, statistically (306.21±2.783 kg). In the same study, the carcass weight of Charolais was given as 323.22±7.333 kg, which is approximately 40 kg lower than the average obtained in our study.…”
Section: Resultsmentioning
confidence: 95%